(untitled) - Eksteen, Liana

Essential oils and fenugreek cotyledon extract as natural alternatives to ionophore antibiotics: the effect on growth performance, carcass quality and profitability in feedlot cattle (Stellenbosch : Stellenbosch University, 2025)
Thesis (MScAgric)--Stellenbosch University, 2025.